Exigência de lisina para alevinos de tambaqui - SILVA, Janayra Cardoso (2016)
Aquaculture is one of the activities that has continuous growth each year, due to increased global demand for fish meatand the reduction of natural stocks. Therefore, knowledge of the nutritional requirements of the species with productive potential, such as tambaqui, it becomes necessary. This study aimed to evaluate the requirement of digestible and total lysine in the feed fingerlings tambaqui (Colossoma macropomum). We used 750 fingerlings of tambaqui with initial weight of 0.34 ± 0.02g in an experiment using a randomized block design, with six treatments, five replicates in two blocks and twenty-five fish per plot. The treatments were six isocaloric experimental diets, isocalcium and isophosphoric with different levels of digestible lysine (1.300; 1.480; 1.600; 1.840; 2.020; and 2.200%), formulated using the technique of "amino acid supplementation," based on the ideal protein concept. The fish were kept in polythene containers (tanks) equipped with individual water supply and aeration, and were fed ad libitum in six meals a day for 50 days. They evaluated the performance parameters, feed efficiency, daily positions of body protein and fat and nitrogen retention efficiency. The feed intake, crude protein intake to the rate of specific crecimento and body composition (moisture, protein and fat) and the deposition of body fat of fish not vary due to the increase of digestible lysine levels in the diet. For weight gain and body protein deposition fish, the lysine level estimated by the feed of the first intersection of the quadratic equation obtained by the LRP plateau model was 1.73 and 1.78%, respectively. The digestible lysine linearly increased and lysine efficiency for weight gain linearly decreased due to the increase of digestible lysine levels in the diet. To feed conversion and nitrogen retention efficiency, the best results were obtained with the level of 1.66% and 1.84% digestible lysine, respectively. It is concluded that the recommendation of lysine levels in rations to tambaqui fingerlings is 1.73% and 1.78%, equivalents to 1.95% and 2.00% of total lysine, for providing better weight gain and body protein deposition, respectively, in the phase of 0.34 to 5.67g.